Measurement of differential top-quark-pair production cross sections in pp collisions at √s = 7TeV - Chatrchyan, S; Chatrchyan, S; Khachatryan, V; Khachatryan, V; Sirunyan, A; Sirunyan, A; Tumasyan, A; Tumasyan, A; Adam, W; Adam, W; Aguilo, E; Aguilo, E; et al. (2013)
Normalised differential top-quark-pair production cross sections are measured in pp collisions at a centre-of-mass energy of 7 TeVat the LHC with the CMS detector using data recorded in 2011 corresponding to an integrated luminosity of 5. 0 fb-1. The measurements are performed in the lepton+jets decay channels (e+jets and μ+jets) and the dilepton decay channels (e+}e-, μ+μ-, and μ±e∓). The tt̄ differential cross section is measured as a function of kinematic properties of the final-state charged leptons and jets associated to b quarks, as well as those of the top quarks and the tt̄ system. The data are compared with several predictions from perturbative QCD calculations up to approximate next-to-next-to-leading-order precision. No significant deviations from the standard model are observed. © 2013 CERN for the benefit of the CMS collaboration.